Modelo unidimensional da transferência de calor transiente em oleodutos durante parada de produção - Silva, Agnes Batoqui Costa e (2018)
Oil is the world's main energy source and the representativeness of its exploration on offshore fields has been growing, in increasingly deeper waters, bringing new challenges to the oil industry. Among the major challenges is the wax deposition on the pipe wall, a process that occurs due to the heat transfer heat between the oil and the external marine environment, this deposition is intensified during shutdowns. In this work, the objective is a one-dimensional study of the oil cooling in a subsea pipeline after shutdown. Through mathematical modeling and numerical-computational modeling with discretization by the Finite Volumes Method, an algorithm was implemented in MATLAB®, to simulate the cooling of the oil-pipe-seawater system and the results obtained were analyzed. Different case studies were analyzed, initially the efficiency of the method used was verified, than the discrepancy of the temperature variation between pipes without insulation and pipe-in-pipe were checked, and finally the analysis gives a forecast of the time necessary after a shutdown to the paraffin begins to be deposited in the pipeline. This prediction is very useful, as it helps from the development stage of oil production in offshore fields, to the determination of interventions in line.